2016
DOI: 10.1097/md.0000000000005670
|View full text |Cite
|
Sign up to set email alerts
|

The association between various indices of obesity and severity of atherosclerosis in adults in the north of Iran

Abstract: Recent observational studies have reported controversial results for the association between different anthropometric indices of obesity and severity of atherosclerosis. The aim of the current study is to determine the associations between anthropometric indices with severity of atherosclerosis in adult population in north of Iran.The cross-sectional study was performed on 610 participants, who were admitted to a hospital for elective angiographyin Rasht, Iran, Anthropometric indices, including waist circumfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
(33 reference statements)
1
8
0
Order By: Relevance
“…There is a consensus whereby, to measure the success of any intervention in programs for modifying the body composition, single indicators like weight loss or BMI should not be used. Evidence has shown that body weight per se cannot be considered to be reliable [13]. Instead, parameters representing the quality of the weight loss, such as muscle mass gain or body fat loss, should be used [14].…”
Section: Introductionmentioning
confidence: 99%
“…There is a consensus whereby, to measure the success of any intervention in programs for modifying the body composition, single indicators like weight loss or BMI should not be used. Evidence has shown that body weight per se cannot be considered to be reliable [13]. Instead, parameters representing the quality of the weight loss, such as muscle mass gain or body fat loss, should be used [14].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, in a recent study on 610 healthy Iranian adults, Salari et al ( 34 ) report no independent association between obesity indices and atherosclerosis. In addition, results of a cross-sectional study on 120 subjects undergoing coronary angiography showed that anthropometric measurements could not be markers of atherosclerosis in subjects with overweight/obesity ( 35 ).…”
Section: Discussionmentioning
confidence: 86%
“…The average age distribution of patients in the current study was mostly in the sixth decade (60); the result seems similar to those of previous studies. 11,12 This might be the most frequent complications that occur and appear at the mentioned age group. Concerning gender, this study revealed that CAPs percentage in males was slightly higher (51%) than females (48%).…”
Section: Resultsmentioning
confidence: 94%